Centella asiatica L. Urban protects against morphological aberrations induced by chronic unpredictable mild stress in rat's hippocampus via attenuation of oxidative stress. Issue 1 (31st December 2022) - Jagadeesan, Saravanan; Chiroma, Samaila Musa; Mohd Moklas, Mohamad Aris; Hidayat Baharuldin, Mohamad Taufik; Mat Taib, Che Norma; Amom, Zulkhairi; Vishnumukkala, Thirupathirao; Thomas, Warren; Mahdi, Onesimus
ABSTRACT: The present study evaluated the effect of Centella asiatica L. Urban (CA) extracts on ultrastructure and oxidative stress parameters on chronic unpredictable mild stress (CUMS) rat's hippocampi. Rats were divided into six groups (n=6) and treated as follows: Group 1, Unstressed + normal saline (control); Group 2, CUMS + normal saline (Model); Group 3, CUMS + Flx (10 mg/kg) (FLX); Groups 4, CUMS + CA (200 mg/kg) (CA 200); Group 5, CUMS + CA (400 mg/kg) (CA 400) and Group 6, CUMS + CA (800 mg/kg) (CA 800). Nine different stressors were administered to the rats for 8 weeks consecutively, with concurrent administration of fluoxetine or CA. The hippocampi of the rats were evaluated by transmission electron microscopy (TEM) and oxidative stress biomarkers were also determined. Qualitative TEM results showed defective mitochondria, nucleus, myelin sheaths and reduced numbers of synapses in CUMS rats as well as increased oxidative stress biomarkers. Administration of CA prevented some of the structural and biochemical aberrations observed in response to stress in a manner comparable with fluoxetine, a selective serotonin-reuptake inhibitor. Conclusively, CA ameliorates structural defects induced by CUMS in the rat hippocampus, with a potential therapeutic importance in the treatment of stress and depression.